Detection of Apoptosis at the Single-Cell Level by Direct Incorporation of Fluorescein-dUTP in DNA Strand Breaks. (April 1996) - Piqueras, Bernard; Autran, Brigitte; Debre, Patrice; Gorochov, Guy
Apoptosis induced in different cell lines can be detected and quantified in one step. Direct labeling of apoptotic cells (DLAC) was performed by incorporation of fluorescein-dUTP (F-dUTP) in DNA strand breaks by terminal deoxynucleotidyl transferase (TdT). Nick-end-labeling using F-dUTP obviates the need for second-step revelation reagents without reducing the specificity of detection. Cells were analyzed by microscopy or flow cytometry for objective quantification of apoptotic cells in controlled dilution samples. Furthermore, we demonstrate that DLAC is compatible with surface labeling by monoclonal antibodies, allowing dual-color analysis. The data presented here illustrate the simplicity and potential of this method, which allows the preservation of fragile cells and the possibility of combining apoptosis detection with immunostaining.